2005
DOI: 10.1113/jphysiol.2005.095331
|View full text |Cite
|
Sign up to set email alerts
|

Actions of brain‐derived neurotrophic factor on spinal nociceptive transmission during inflammation in the rat

Abstract: The aim of the current study was to investigate whether, and if so how, brain-derived neurotrophic factor (BDNF) acts to develop the spinal sensitization underlying inflammation-induced hyperalgesia. In spinal cord slice preparations from rats with inflammation induced by complete Freund's adjuvant (CFA), BDNF, but not nerve growth factor (NGF) or neurotrophin-3 (NT-3), acted presynaptically to increase the frequency of excitatory miniature EPSCs in substantia gelatinosa (SG) neurones of the CFA-treated, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 29 publications
1
58
0
4
Order By: Relevance
“…In keeping, pharmacological experiments have demonstrated that the plastic changes in spinal cord sensory pathways that follow inflammation, can be blocked by a trkB-IgG fusion protein sequestering BDNF . Moreover, evidence has been provided that BDNF, acting on trkB receptors, causes an increase of spontaneous glutamate release in dorsal horn lamina II, both in control animals and during inflammation (Bardoni et al, 2004;Matayoshi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In keeping, pharmacological experiments have demonstrated that the plastic changes in spinal cord sensory pathways that follow inflammation, can be blocked by a trkB-IgG fusion protein sequestering BDNF . Moreover, evidence has been provided that BDNF, acting on trkB receptors, causes an increase of spontaneous glutamate release in dorsal horn lamina II, both in control animals and during inflammation (Bardoni et al, 2004;Matayoshi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found in the central nerve terminals of primary afferent fibers [32]; neuropathic pain-related behaviors, such as allodynia, are attenuated by blocking or sequestering BDNF [24,33]. Also, following nerve injury, the expression of BDNF and its high-affinity receptor, TrkB, are upregulated in the superficial dorsal horn [34][35][36][37][38][39].…”
Section: Brain-derived Neurotrophic Factor Mimics the Effects Of Chromentioning
confidence: 97%
“…Although it was already established that neuropathic painrelated behaviors, such as allodynia, are attenuated by blocking or sequestering BDNF [24,33], demonstrating that such manipulations prevent the development of the CCI "footprint" would be practically rather difficult. Essentially all of the works done in establishing the "footprint," which required recording and extensive data analysis from hundreds of substantia gelatinosa neurons [27], would need to be repeated after multiple in vivo intrathecal injections of BDNF blockers.…”
Section: Similarity Of Pharmacologymentioning
confidence: 98%
See 1 more Smart Citation
“…Efforts to antagonize the effects of BDNF by use of anti-BDNF antiserum or a trkB-IgG construct have been successful in models of neuropathic pain and inflammatory hypersensitivity (Matayoshi et al, 2005). However, to date, no small-molecule antagonists of BDNF have been described.…”
mentioning
confidence: 99%